Amplifying mRNA vaccines: potential versatile magicians for oncotherapy - Hu, Chaoying; Liu, Jianyang; Cheng, Feiran; Bai, Yu; Mao, Qunying; Xu, Miao; Liang, Zhenglun (Frontiers in Immunology, 2023)
Cancer vaccines drive the activation and proliferation of tumor-reactive immune cells, thereby eliciting tumor-specific immunity that kills tumor cells. Accordingly, they possess immense potential in cancer treatment. However, such vaccines are also faced with challenges related to their design and considerable differences among individual tumors. The success of messenger RNA (mRNA) vaccines against coronavirus disease 2019 has prompted the application of mRNA vaccine technology platforms to the field of oncotherapy. These platforms include linear, circular, and amplifying mRNA vaccines. In particular, amplifying mRNA vaccines are characterized by highlevel and prolonged antigen gene expression at low doses. They can also stimulate specific cellular immunity, making them highly promising in cancer vaccine research. In this review, we summarize the research progress in amplifying mRNA vaccines and provide an outlook of their prospects and future directions in oncotherapy.